2020
DOI: 10.1038/s41598-020-59223-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term observations from Antarctica demonstrate that mismatched scales of fisheries management and predator-prey interaction lead to erroneous conclusions about precaution

Abstract: Low catch limits for forage species are often considered to be precautionary measures that can help conserve marine predators. Difficulties measuring the impacts of fisheries removals on dependent predators maintain this perspective, but consideration of the spatio-temporal scales over which forage species, their predators, and fisheries interact can aid assessment of whether low catch limits are as precautionary as presumed. Antarctic krill are targeted by the largest fishery in the Southern Ocean and are key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
95
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(99 citation statements)
references
References 45 publications
4
95
0
Order By: Relevance
“…Krill fishing may play a significant role in Chinstrap penguin population dynamics, especially at local scales 17 . Multiple studies have documented overlap between commercial krill trawls and penguin foraging ranges 16,31,32 . Because they make marginally longer foraging trips than Adélie or Gentoo penguins, Chinstrap penguins could have higher exposure to fishing interference during the breeding season.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Krill fishing may play a significant role in Chinstrap penguin population dynamics, especially at local scales 17 . Multiple studies have documented overlap between commercial krill trawls and penguin foraging ranges 16,31,32 . Because they make marginally longer foraging trips than Adélie or Gentoo penguins, Chinstrap penguins could have higher exposure to fishing interference during the breeding season.…”
Section: Discussionmentioning
confidence: 99%
“…Because they make marginally longer foraging trips than Adélie or Gentoo penguins, Chinstrap penguins could have higher exposure to fishing interference during the breeding season. Watters et al 32 predicted that today's "precautionary" limits on krill fishing would affect penguin breeding success with a similar magnitude to climate change, if seasonal local harvest rates exceed a threshold of 0.1. This is especially pertinent to Chinstrap penguin colonies adjacent to krill-fishing hotspots, though continued declines in areas currently experiencing less intense krill trawling (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The seasonal influx of potentially vast numbers of spatially unconstrained krill predators that are unaccounted for in current assessments could have implications for disentangling the key drivers of ecosystem processes. In the context of the WAP, these processes are often characterised by models linking predator performance indices, large-scale climate processes and fishing effort 13 16 with many being underpinned by model parameter estimates that neglect male AFS below reproductive age 17 .…”
Section: Introductionmentioning
confidence: 99%
“…The former is consistent with CCAMLR's mandate to protect populations that are dependent upon krill. Indeed, long-term observations of colonies of krill-feeding penguins around the South Shetland Islands have shown that in some years fishing can cause detectable negative impacts on these colonies 19 .…”
mentioning
confidence: 99%